2016
DOI: 10.3390/ijms17101564
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Copper Chlorophyllin Immobilization onto Hippospongia communis Marine Demosponge Skeleton and Its Antibacterial Activity

Abstract: In this study, Hippospongia communis marine demosponge skeleton was used as an adsorbent for sodium copper chlorophyllin (SCC). Obtained results indicate the high sorption capacity of this biomaterial with respect to SCC. Batch experiments were performed under different conditions and kinetic and isotherms properties were investigated. Acidic pH and the addition of sodium chloride increased SCC adsorption. The experimental data were well described by a pseudo-second order kinetic model. Equilibrium adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
(75 reference statements)
1
20
0
Order By: Relevance
“…Moreover, for the obtained hybrids, independently of the initial concentration of chlorophyllin used and the duration of the adsorption process, the efficiency of adsorption is maintained constantly high. Our observations are in agreement with Norman et al (2016), who also observed the high efficiency of chlorophyllin adsorption on the natural biopolymer H. communis.…”
Section: Adsorption Efficiency and Stability Of Tio 2 -Sio 2 / Chlorosupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, for the obtained hybrids, independently of the initial concentration of chlorophyllin used and the duration of the adsorption process, the efficiency of adsorption is maintained constantly high. Our observations are in agreement with Norman et al (2016), who also observed the high efficiency of chlorophyllin adsorption on the natural biopolymer H. communis.…”
Section: Adsorption Efficiency and Stability Of Tio 2 -Sio 2 / Chlorosupporting
confidence: 93%
“…Farag et al (2012) also reported that the first loss of the mass in the chlorophyllin degradation may be related to the evaporation of residual adsorbed water. The second mass loss of about 49% in the temperature range 250-500 °C, also observed by Norman et al (2016), is associated with the elimination of Cu 2+ ions. This degradation step was also mentioned by Farag et al (2012) work.…”
Section: Thermal Analysismentioning
confidence: 55%
See 3 more Smart Citations